PENGARUH SELEBRITI DALAM PENCALONAN ANGGOTA LEGISLATIF TERHADAP PERILAKU PEMILIH: STUDI KASUS PENCALONAN KOMENG SEBAGAI ANGGOTA DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA DAPIL KOTA BEKASI 4 TAHUN 2024 - Alamsyah, Fadzli Ramadhan; marlina, neny - (Journal of Politic and Government Studies, 2025)
This study investigates the influence of celebrities on voter behavior in the context of Komeng's candidacy as a member of the Regional Representative Council (DPD) of the Republic of Indonesia for the Bekasi 4 electoral district in the 2024 elections. Employing a quantitative approach with a sample of 100 respondents, the research analyzes data through a series of statistical tests, including validity and reliability tests of the instruments, classical assumption tests, correlation tests, and simple linear regression tests. The findings indicate a significant and positive relationship (r = 0.805) between celebrity influence and voter behavior, suggesting a strong impact. However, the level of celebrity influence is classified as moderate, with 78% of respondents feeling the impact of celebrities in their decision-making process. Further analysis reveals that the attractiveness and positive reputation of Komeng as a celebrity play a crucial role in attracting attention and building trust among voters. Sociological factors such as gender, ethnic background, and religious values were also found to influence voter behavior, while rational considerations like personal and national economic conditions were relatively less dominant. Another intriguing finding is the prevalence of celebrity influence among the productive age group (18-45 years), which indicates a tendency to choose candidates based solely on popularity, without considering other important aspects. This study suggests the need for increased political literacy and critical awareness among voters so they can comprehensively evaluate candidates, taking into account their vision, mission, work programs, and track record, rather than just their popularity. Future research is recommended to further explore the role of social media and local issues in shaping voter behavior in Indonesia, as well as to expand the scope of the study to other electoral districts and candidates for broader generalization